Health equity in urban and rural settings: implementation of the place standard tool in Spain - Ocaña-Ortiz, Ana; Gea-Caballero, Vicente; Juárez-Vela, Raúl; Peiró, Rosana; Pérez-Sanz, Elena; Santolalla-Arnedo, Iván; Sufrate-Sorzano, Teresa; Garrote-Cámara, María Elena; Paredes-Carbonell, Joan Josep (Frontiers in Public Health, 2024)
The physical, social, and economic characteristics of neighborhoods and municipalities determine the health of their residents, shaping their behaviors and choices regarding health and well-being. Addressing local environmental inequalities requires an intersectoral, participatory, and equity-focused approach. Community participation plays a vital role by providing deeper insights into local contexts, integrating community knowledge and values into processes, and promoting healthier, fairer, and more equitable actions. In recent years, various tools have been developed to assess places and transform them into health-promoting settings. One such tool, the Place Standard Tool (PST), facilitates discussions on Social Determinants of Health grouped into 14 themes, serving as a starting point for local health interventions. In this study, that took place between August 2019 and February 2020, we described the resident’s perceptions of two municipalities in the Valencian Community, Spain, using the validated Spanish version of the PST. A mixed-method convergent-parallel design was used to gain a holistic insight into residents’ experiences concerning their physical, economic, and social environment. A total of 356 individuals from both municipalities participated in the study through discussion groups, structured interviews, and online survey. Descriptive analysis of the individual questionnaire answers was conducted, and differences between municipalities were explored. Qualitative thematic analysis was conducted on structured interviews and discussion groups. Quantitative and qualitative data were integrated to facilitate their comparison and identify areas of convergence or divergence in the findings. Overall, rural areas received more favorable evaluations compared to urban ones. Public Transport as well as Work and Local Economy were consistently rated the lowest across all groups and contexts, while Identity and Belonging received the highest ratings. In the urban area, additional negative ratings were observed for Traffic and Parking, Housing and Community, and Care and Maintenance. Conversely, Identity and Belonging, Natural Spaces, Streets and Spaces, Social Interaction, and Services emerged as the highest-rated themes overall. In the rural context, positive evaluations were given to Walking or Cycling, Traffic and Parking, Housing and Community, and Influence and Sense of Control. Significant differences (p < 0.01) between urban and rural settings were observed in dimensions related to mobility, spaces, housing, social interaction, and identity and belonging. Our study illustrated the capacity of the PST to identifying aspects within local settings that influence health, revealing both positive and challenging factors. Successful implementation requires appropriate territorial delineation, support from local authorities, and effective management of expectations. Furthermore, the tool facilitated community participation in decision-making about local environments, promoting equity by connecting institutional processes with citizen needs.